Efficient one-pot synthesis of 2,2-dimethyl-2H-chromenes via pd(II)-catalyzed coupling and SiO2-promoted condensation of o-halophenols with 2-methyl-3-buten-2-ol - Tee, Jia Ti; Yaeghoobi, Marzieh; Chee, Chin Fei; Abd Rahman, Noorsaadah (Taylor & Francis, 2015)
An efficient synthesis of 2,2-dimethyl-2H-chromenes was accomplished by Pd(II)-catalyzed coupling and SiO2-promoted condensation of o-halophenols with 2-methyl-3-buten-2-ol (1,1-dimethylallyl alcohol) in one pot. The method is very general and can be useful for the synthesis of some natural 2,2-dimethyl-2H-chromenes.